2008
DOI: 10.1016/j.neuroscience.2008.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Group II metabotropic glutamate receptor activation attenuates peripheral sensitization in inflammatory states

Abstract: Several lines of evidence indicate that Group II metabotropic glutamate receptor (mGluR) activation can depress sensory transmission. We have reported the expression of Group II mGluRs on unmyelinated axons, many of which were presumed to be nociceptors, in the rat digital nerve (Carlton et al., 2001b). The goals of the present study are to further our understanding of Group II modulation of nociceptor processing in the periphery, documenting behavioral changes using inflammatory models and documenting, for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 61 publications
(90 reference statements)
1
30
0
Order By: Relevance
“…Previous work demonstrated that application of APDC into the rodent skin reduced the duration and magnitude of inflammatory pain responses, indicating a peripheral mechanism for the analgesic action [16; 54]. Group II mGluR activation also prevented PGE 2 -induced potentiation of capsaicin-evoked calcium responses [53], and reduced capsaicin-evoked nociceptive fiber activity, suggesting that the anti-nociceptive effect may be related to inhibition of the heat- and capsaicin-sensitive ion channel TRPV1 [3; 6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work demonstrated that application of APDC into the rodent skin reduced the duration and magnitude of inflammatory pain responses, indicating a peripheral mechanism for the analgesic action [16; 54]. Group II mGluR activation also prevented PGE 2 -induced potentiation of capsaicin-evoked calcium responses [53], and reduced capsaicin-evoked nociceptive fiber activity, suggesting that the anti-nociceptive effect may be related to inhibition of the heat- and capsaicin-sensitive ion channel TRPV1 [3; 6].…”
Section: Discussionmentioning
confidence: 99%
“…In several rodent models of inflammatory and neuropathic pain, pharmacological activation of group II mGluRs reduced nocifensive behaviors [33; 35; 43; 54]. Immunoreactivity for group II mGluRs has been observed in rodent DRG neurons [4; 5], and cutaneous administration of a group II mGluR agonist suppressed capsaicin-evoked activity in nociceptors, indicating a peripheral mechanism of action [3; 16; 53]. Interestingly, pharmacological inhibition of peripheral group II mGluRs prolonged hyperalgesia and nociceptor activity, suggesting that group II mGluRs act endogenously to reverse hypersensitivity [6; 54].…”
Section: Introductionmentioning
confidence: 99%
“…Group II and III mGluRs are expressed by primary sensory neurons (Carlton et al, 2001a; Carlton and Hargett, 2007), and peripheral injection of a Group II agonist inhibits peripheral nociceptor activity (Du et al, 2008), in particular transient receptor potential vanilloid 1 (TRPV1)-induced pain behaviors and TRPV1-induced excitation and sensitization of peripheral nociceptors (Carlton et al, 2009a). Thus, exogenous activation of peripheral mGluRs modifies pain transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are found to be therapeutically active, but are associated with side effects like psychomimetic symptoms, cognitive impairment, dizziness and sedation [7,48]. Newer approaches have been identified to overcome these side effects, which include, inhibiting other binding sites of NMDA receptor like the NR2B, glycine B site [49][50][51][52][53][54][55][56][57][58][59][60][61][62], targeting other receptors like AMPA [63][64][65][66][67], kainate [68][69][70][71][72] and mGluR1 -5 [73][74][75][76][77][78][79][80][81][82], enhancing the activity of glutamate transporters that sequester the extracellular glutamate [23,24,83] and inhibiting glutamate release by designing various enzyme inhibitors [84][85][86][87][88][89][90][91...…”
Section: Glutamatergic System As a Target For Neuropathic Painmentioning
confidence: 99%
“…Among the drugs acting on group II mGlu receptor, a mGluR2/3 agonist LY379268 (35, Figure 5) and mGluR7 agonist AMN082 (36, Figure 5) have been shown to attenuate allodynia and hyperalgesia on day seven after CCI in swiss albino mice [77]. A selective group-II mGluR agonist, 4-aminopyrrolidine-2-,4-dicarboxylate (APDC) (37, Figure 5) attenuated peripheral sensitization in inflammatory states [80] and mechanical hyperalgesia in neuropathic pain model [81]. ACPT-I (38, Figure 5), a selective group III mGluR agonist has also been found to inhibit hyperalgesia in various animal models of inflammation and neuropathic pain [82].…”
Section: Metabotropic Glutamate Receptor Modulatorsmentioning
confidence: 99%